Decision‐Making Preferences in Times of Crisis - Réka Várnagy; Anna Novák; Judit Badics (Politics and Governance)
During crises, understanding political decision-making processes and evaluating related preferences are key to the legitimacy of political decisions. Our research focuses on preferences in decision-making processes in times of crisis through the analysis of the representational style most preferred by voters: that is, whether they prefer representation of the public good by the representatives, the party lines, the involvement of experts, or the incorporation of voters’ interests. Within the framework of representative democracy, these decisions are mediated by representatives whose representational style determines whose interest and opinion decision-making processes integrate. In our analysis, we examined representative styles in the context of three different types of crises: economic, social, and environmental. Our results indicate that the type of crisis is indifferent when it comes to preferred political decision-making processes, as Hungarian voters tend to favor processes where they are being consulted by the representatives across different scenarios. Representatives’ commitment to party lines is disfavored when making political decisions and we observed there is no clear preference regarding the involvement of experts in political decisions in times of crisis. These observed preferences strongly contradict the prevailing “strong party discipline” in Hungary. This deviation accentuates both weakening representative linkages and the importance of the performative elements of representation feeding into the populist characteristic of Hungarian democracy.